PENGEMBANGAN LKS MATEMATIKA BERBASIS MASALAH UNTUK KELAS VIII SMP PADA MATERI PERSAMAAN LINEAR DUA VARIABEL - yani, sabar (Universitas Pasir Pengaraian, 2016)
This study aims to produce problem-based learning math worksheets valid and practical in the material system of linear equations of two variables. This type of research was the development of 3-D research Stages in this study consisted of: pendefenisian stage (Define), the design phase (Desaign) and stage of development (Development). The subjects were students of class VIII SMP N 1 Kepenuhan in the 1st half semester of the school year 2014/2015. The instrument used in this study was a validation questionnaire sheet and questionnaire sheet practicalities. The results showed the product LKS math learning system of linear equations in two variables produced viable as teaching materials math learning the material system of linear equations in two variables of class VIII SMP two based on the results of the assessment kelayakannnya by four validator with some revisions and corrections then obtained an average score results Problem-based validation LKS avarage of 3.04 with a valid category, based on the practicalities of using angkrt test, observation of the implementation of learning the importance of the average scores based on the results of the practicalities of LKS issue average fo 88% with the category of very practical. So it can be concluded that the problem-based LKS declared valid and very practical.